The current situation and prospect of China’s rural revitalization research: A quantitative analysis based on literature - Longyuan, Bao; Jun, Mei; Pei, Hou (The Journal of Humanities & Social Sciences, 2022)
As an important development strategy, the rural revitalization strategy is being vigorously promoted in China. This paper has researched into the existent conditions and trends with a quantitative analysis on 4,935 journal papers related to rural revitalization in China via CiteSpace. The result shows a rapid upward. However, the institutional cooperation is low and the core research group has not been formed. The research topics mainly focus on rural governance, poverty alleviation, integrated development of urban and rural areas, etc. The topics, perspectives and methods of the research show the characteristic of interdisciplinary intersection. China’s rural revitalization research is transitioning from theoretical interpretation and theoretical analysis to empirical research and micro-research. In the future, it is very necessary and meaningful for China’s rural revitalization to strengthen academic research cooperation, deepen research topics, broaden research ideas and enrich research methods.